HASIL PADI GOGO LOKAL-NTT DI BAWAH KONDISI DEFISIT AIR - Welianto Boboy; Yos F. da-Lopes (Politeknik Pertanian Negeri Kupang, 2010)
Yield of NTT Local Upland Paddy under Water Deficit Conditions. This study was to evaluate yield of NTT local upland paddy under drought stress at different growth phases. The research was design in Randomized Block Design, consisted of two factors, i.e. upland paddy cultivars (factor A) and drought stress at different growth phases (factor B). Factor A consists of nine cultivars i.e. Kodi-1, Kodi-3, Kodi-4, Mts-3, Mts-5 Wkb-1, Wkb-2, IR-64, and Grogol; Factor B consists of four levels i.e. control (without drought stress treatment, P0), drought stress of 1 x 120 hours at vegetative growth phase (P1), drought stress treatment of 1 x 120 hours at the generative growth phase (P2), drought stress of 1 x 120 hours at the vegetative and generative phase (P3). Each treatment was repeated three (three) times so there were 108 observation units. The parameters measured were the number of grains per panicle, pithy grain percentage, and dry weight of 100 pithy grains. All the measurement data of each variable were analyzed using analysis of variance (ANOVA) and followed by Duncan multiple range test (DMRT) when there were significant differences among the treatment being tested. The results showed that there were different interaction among NTT local upland paddy cultivars due to the drought stress at different growth phases, in the terms of number of grains per panicle, pithy grain percentage, and dry weight of 100 pithy grains. Based on the number of grains per panicle, Grogol was tolerant to drought stress; whereas, Wkb-2, Wkb-1, and IR-64 were sensitive to drought stress. Refers to the percentage of pithy grains, grogol, MTS-3, and MTS-5 were tolerant to drought stress; meanwhile, Kodi-4 and Wkb-1 were the most sensitive cultivars.Keywords: local upland paddy, drought stress, growth phases